(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Work quality of the grain cleaning machines depends on work indicators of the sieve. Based on this, longitudinal-transverse oscillation sieve developed for grain cleaning machine. The developed sieve researched theoretically and experimentally. According to the researches, it was defined that the longitudinal oscillation of the grain-cleaning sieve nfr = 140 – 175 rpm, the amplitude of the longitudinal oscillations Al =30 mm, the amplitude of the transverse oscillations At = 3 – 5 mm, and the slope angle αs=14о. In these operating parameters work indicators of the sieve consisted of the grain losses is not more than 0.5 % and cleaning efficiency is 99.6 %.